Pengkajian dan Penanganan Daerah Aliran Sungai dengan Pendekatan Model Answers Bagian H : Prediksi Erosi, dan Sedimentasi - Suharyono Suharyono; Putu Sudira; Sukirno Sukirno (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1998)
The amount of sediment which will leave to or deposit in the elements of watershed was able to be calculated by ANSWERS model at different land uses, soil types and land slopes. The simulation model resulted the soil erosion of 2,228 WOK' or equal to 51,99 ton/ha/year at the existing rainfall (21,95 mm). Considering the tolerable soil erosion of the study area of 30 ton/ha/year, the optimal forest land area needed in this watershed is 70% of the total land area, where the soil erosion is still less than the tolerable soil erosion, that is 21, 98 ton/ha/year. This value is less than 58,77% of the existing soil erosion